(untitled) (Mongolian Journal of International Affairs, 2024)
When the Russian President Vladimir Putin made world shocking visit to International Criminal Court member state for the first time since his arrest warrant in 2023. One of his visit purposes was to commemorate 85th anniversary of Khalkhiin gol War. After a fall of Soviet Union, Soviet-satellite country faced their own destiny to run sovereign foreign policy without directive from Kremlin. Mongolia has unique geographic setting, located between two authoritarian nuclear power competing with the west. Mongolian diplomats effectively used their favorable period as two neighbors not paying strong attention to their buffer state to find long lasting solution for security assurance. The country chosen neutral, multi pillared, open and peaceful foreign policy principles through political-diplomatic means. After 85 years, international atmosphere becoming more dismal and even risky for small and medium states. Current situation highlights importance of studying the geopolitical settings and consequences of Khalkhiin Gol War. Following paper discusses prewar geopolitical settings and causes using bargaining theory.